Analisis Kebijakan Investasi, Kebijakan Hutang, Kebijakan Dividen dan Nilai Perusahaan Sektor Energi - Febriana, Silfani Ajeng; Koesoemasari, Dian S.P.; Nirmala, Nirmala (Studi Ekonomi dan Kebijakan Publik, 2024)
Purpose: This research aims to partially analyze the influence of investment policy, debt policy and dividend policy on firm value in energy sector companies listed on the IDX for the 2018-2022 period. Methodology: This research uses quantitative methods. The population in this research was 75 companies. The sample was obtained using a purposive sampling technique of 14 companies. The data used in this research is secondary data from energy sector companies listed on the Indonesian Stock Exchange in 2018-2022, the amount of data is 70. The analytical tool used in this research is panel data regression with the help of E-views 12 software. Results: The results of this study show that investment policy and dividend policy have a positive significant effect on firm value, while debt policy does not have a significant effect on firm value. Limitations: The limitation of this research is that the value of the coefficient of determination (R²) is only 62.05%, which is still relatively low because it is below 80%. Besides that, there is one hypothesis that can not be proven, namely the debt policy variable. Contribution: This research can be used as consideration for investors before investing because the three company policies, namely investment policy, debt policy and dividend policy can provide an overview of the firm's condition.